Multi-type Air Pollutant Emission Inventory of Non-road Mobile Sources in China for the Period 1990–2017 - Xianbao Shen; Lei Kong; Yue Shi; Xinyue Cao; Xin Li; Bobo Wu; Hanyu Zhang; Zhiliang Yao (Aerosol and Air Quality Research)
Abstract With the increasingly strict supervision of road mobile sources and the ongoing progress in research, the relative contribution of non-road mobile sources to the total emissions has grown in prominence. Therefore, accurately estimating the emissions from non-road mobile sources is essential to developing effective policies for improving air quality. Hence, this study established an inventory of nine air pollutants, viz., CO, NOx, HC, PM2.5, PM10, BC, OC, VOCs, and SO2, emitted by four types of non-road mobile sources, viz., construction machinery, agricultural machinery, vessels, and diesel locomotives, in China for the period 1990–2017. These emissions increased continually from 1990 till 2014, after which they decreased before increasing again during 2017. With the exception of SO2, which primarily originated from vessels, agricultural machinery accounted for the largest proportion of emissions for all of the pollutants, contributing 67.7% (1472.5 Gg) and 46.1% (2170.4 Gg) of the total CO and NOx from non-road mobile sources, respectively. Additionally, the spatial distribution of the investigated pollutants revealed high concentrations on the North China Plain and in the Southeast China coastal area. Our findings demonstrate the necessity of improving the registration system for non-road mobile sources as well as the urgency of obtaining accurate emission factors for them by further researching their emission characteristics.